A season in hell - Higgins, Jack, 1929- (London : Pan Books, 1989)
Sarah Talbot enlists a former SAS sergeant Sean Egan to uncover the circumstances surrounding her stepson Eric's death. They embark on a quest for revenge, that leads from London to Paris, to Sicily and Northern Ireland and back to London.
Keywords: Thrillers (Fiction).; Revenge -- Fiction; Special forces (Military science) -- Fiction; Suspense fiction